PEMANFAATAN EDIBLE COATING BERBAHAN KITOSAN UNTUK MENCEGAH PERKEMBANGAN BOTRYTIS CINEREA PADA BUAH TOMAT CHERRY - Primayuri, Deviana; Sundari, Dini; Purba, Dumaris Priskila (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Botrytis cinerea, a fungal pathogen, is largely to blame for the significant decline in cherry tomato prices. Chitosan, a natural biopolymer, has been explored as an alternative coating material to enhance fruit resistance and preserve postharvest quality. This study looks at how well chitosan edible coatings, applied by spraying and dipping, can prevent Botrytis cinerea infection on cherry tomatoes. The fruits were intentionally infected by making cuts and soaking them in a solution containing the pathogen, and then they were treated with chitosan coatings. The coated fruits were incubated at room temperature for 14 days and assessed periodically on days 1, 7, and 14 for weight loss, disease incidence, and sugar content (°Brix). Results showed that the dip coating method significantly reduced weight loss and disease incidence compared to other treatments, with the lowest weight loss recorded at 0.87 grams and disease incidence at 22.22%. The highest sugar content was observed in the uncoated control group (7.23° Brix), indicating that coatings might slightly affect sweetness. Both ways of using chitosan successfully prevented the growth of Botrytis cinerea and kept the quality of cherry tomatoes satisfactory while they were stored. These findings suggest that chitosan edible coatings, especially when applied by dipping, offer a promising, environmentally friendly postharvest treatment to reduce decay and prolong the shelf life of cherry tomatoes.